Physical readiness and performance of adolescents of different somatotype - V. M. Mysiv (Physical Education of Students, 2014)
Purpose: to investigate the rate of puberty, changes in indicators of physical fitness and physical activity at the same somatotype different boys in the age range from 11 to 14 years. Material : 123 teenager were examined. The values of the studied parameters were determined at the beginning of each new school year. Tests were used to assess the major conditional qualities and coordination abilities. Results : the overall physical performance of boys of macrosplanchnic somatotype characterized annual trend towards improvement, except for the period between 11 and 12 years. Significant differences are typical for physical performance, except asthenoid and macrosplanchnic somatotype. Typological features installed due to changes in the studied parameters. Conclusions: noted the need to consider the data in shaping the content of physical education in improving orientation.